(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In this paper, taking into account ergodicity of random processes in material processing, information about changes in the technical condition of bearings operating in the same conditions is recorded in the device "Topaz", which allows for frequency analysis of the vibration signal. Vibration measurement was carried out according to the block diagram, which includes a sensor (piezoaccelerometer), an analyzer (Topaz device), a computer with a set of programs for vibration monitoring.